IMPOSITION OF SANCTIONS ANALYSIS OF BUSINESS CRIME CRIMINAL ABORTION - Ngurah Ketut Hendra Gunawan, I Gusti (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2020)
Abortion is misconduct when committed intentionally abort way without any obvious reason to do so. Regarding the crime of abortion is regulated in the Act Positive in Indonesia. Perform abortions should not be just anyone do it because they have to kill the fetus in the womb. In this case I raised the issue that is how the imposition of criminal sanctions against perpetrators of criminal acts of abortion and how the alleviation and prevention of criminal acts of abortion in Indonesia.